The Significance of RHD Genotyping and Characteristic Analysis in Chinese RhD Variant Individuals - Ying, Yanling; Zhang, Jingjing; Hong, Xiaozhen; Xu, Xianguo; He, Ji; Zhu, Faming (Frontiers in Immunology, 2021)
Background RhD is the most important and complex blood group system because of its highly polymorphic and immunogenic nature. RhD variants can induce immune response by allogeneic transfusion, organ transplantation, and fetal immunity. The transfusion strategies are different for RhD variants formed by various alleles. Therefore, extensive investigation of the molecular mechanism underlying RhD variants is critical for preventing immune-related blood transfusion reactions and fetal immunity. Methods RhD variants were collected from donors and patients in Zhejiang Province, China. The phenotypes were classified using the serologic method. The full coding regions of RHD gene were analyzed using the PCR-SBT method. The multiplex ligation-dependent probe amplification (MLPA) assay was used to analyze the genotype and gene copy number. SWISS-MODLE and PyMOL software were used to analyze 3D structures of RhD caused by the variant alleles. The effect of non-synonymous substitutions was predicted using Polymorphism Phenotyping algorithm (PolyPhen-2), Sorting Intolerant From Tolerant (SIFT), and Protein Variation Effect Analyzer (PROVEAN) software. Results In the collected RhD variants, 28 distinct RHD variant alleles were identified, including three novel variant alleles. RH-MLPA assay is advantageous for determining the copy number of RHD gene. 3D homology modeling predicted that protein conformation was disrupted and may explain RhD epitope differential expression. A total of 14 non-synonymous mutations were determined to be detrimental to the protein structure. Discussion We revealed the diversity of RHD alleles present in eastern Chinese RhD variants. The bioinformatics of these variant alleles extended our knowledge of RhD variants, which was crucial for evaluating their impact to guide transfusion support and avoid immune-related blood transfusion reactions.